THE USE OF VISUAL NOVEL VIDEO GAMES AND STUDENTS’ VOCABULARY LEARNING - Mutia, Triyana Bintang (English Education Department of STKIP Pasundan, 2020)
The purpose of this research is to know whether video game is effective to improve or expand vocabulary mastery. This research uses descriptive design. The participant consists of two third grade college students in Bandung. The data were collected by pretest, posttest and an interview. The result of this research indicates that video game is effective enough in the mastery of vocabulary. From the interview result it shows that participants feel happy and feels helped by using this method because for them this method is really fun, interesting and easy to learn. This method really fits for people who don’t really like reading book. The overall results indicate that after using Rewrite visual novel video game the mastery of the participant’s vocabulary increased. The result is retrieved from comparing the result of pretest and that of the posttest.